Molecular and hormonal regulation of angiogenesis in proliferative endometrium - Chianeh, Yousef Rezaei; Rao, Pragna (International Journal of Research in Medical Sciences, 2017)
Angiogenesis is a hallmark of wound healing, the menstrual cycle, cancer, and various ischemic and inflammatory diseases. A rich variety of pro and anti-angiogenic molecules have already been identified. Vascular endothelial growth factor (VEGF) is an interesting inducer of angiogenesis and lymphangiogenesis, because it is a highly specific mitogen for endothelial cells. Signal transduction involves binding to tyrosine kinase receptors and results in endothelial cell proliferation, migration, and new vessel formation. In this article, the role of VEGF and other growth factors in the pathology of dysfunctional uterine bleeding is reviewed. We also discuss the role of VEGF expression and interaction with extracellular matrix that lead to possible inhibition or stimulation of Angiogenic factor on endometrium of dysfunctional uterine bleeding patients.